Digitoflavone Ameliorates Acute Lung Injury via Disturbing the Formation of Functional Stimulator of Interferon Genes Signalosome - Jun-Jie Li; Qing Yao; Ming Dong; Yan Wang; Ye Xiu; Zhi-Xin Wu; Xiao-Mei Zhao; Yin-Kang Wang; Xian-Ling Wang; Yu-Xuan Tian; Xiao-He Xiao; Zhao-Fang Bai (World Journal of Traditional Chinese Medicine)
Objective: The cyclic GMP-AMP synthase (cGAS)-stimulator of interferon (IFN) genes (STING) signaling pathway has been implicated in the initiation and maintenance of a variety of inflammatory diseases. Thus, the search for modulators of the cGAS-STING signaling pathway is likely to contribute to their therapeutic prevention and treatment. Natural products from traditional Chinese medicine are an important source for modern drug development; digitoflavone (DG), a natural flavonoid present in a variety of plants, has been shown to have anti-inflammatory effects. However, its specific mechanisms of action remain unclear and have yet to be used in clinical settings. Materials and Methods: The activation of the cGAS-STING pathway was modeled in bone marrow-derived macrophages (BMDMs) and human leukemia monocytic cell line (THP-1) cells in vivo, and the expression of type I IFN-related genes and pro-inflammatory cytokines was detected after DG pretreatment. Next, we examined the effect of DG on STING downstream signaling events, such as STING oligomerization and functional STING signalosome formation. Using in vivo experiments, the 5,6-dimethylxanthenone-4-acetic acid (DMXAA)-induced agonist and lipopolysaccharide-induced acute lung injury models were used to assay the therapeutic effects of DG. Results: DG effectively inhibited the activation of the cGAS-STING signaling pathway, which was accompanied by an increase in the levels of type I IFN and pro-inflammatory cytokines in BMDMs and THP-1 cells. DG did not affect STING oligomerization but inhibited STING-Interferon Regulatory Factor 3 (IRF3) or TANK-binding kinase 1-IRF3 binding. In addition, DG inhibited the activation of the cGAS-STING pathway induced by DMXAA in vivo, while demonstrating favorable therapeutic effects on acute lung injury. Conclusions: Our results suggest that DG is an inhibitor of the cGAS-STING signaling pathway, which may act by affecting the formation of functional STING signaling pathways. Moreover, the ameliorative effect of DG on acute lung injury could be used to treat cGAS-STING pathway-mediated inflammatory diseases.